The adverse association between stimulant use for attention deficit hyperactivity disorder (ADHD) and semen parameters. (23rd November 2021) - Pham, Minh N.; Hudnall, Matthew T.; Fantus, Richard J.; Lai, Jeremy D.; Ambulkar, Siddhant S.; Wren, James M.; Bennett, Nelson E.; Auffenberg, Gregory B.; Chu, David I.; Brannigan, Robert E.; Halpern, Joshua A.
Abstract: This study examined the relationship between stimulant medications used for the treatment of attention deficit hyperactivity disorder and semen parameters. We performed a retrospective cohort study at a large, academic institution between 2002 and 2020. We included men with a semen analysis without prior spermatotoxic medication use, empiric medical therapy exposure or confounding medical diagnoses (varicocele, Klinefelter's syndrome, cryptorchidism, cystic fibrosis, diabetes, cancer or cancer‐related treatment, and azoospermia). Men were stratified by stimulant exposure (methylphenidate or amphetamines). A multivariable linear regression was fit to assess the association between individual semen parameters, age, stimulant exposure and non‐stimulant medication use. Of 8, 861 men identified, 106 men had active prescriptions for stimulants within 90 days prior to semen testing. After controlling for age and exposure to non‐stimulant medications, stimulant use was associated with decreased total motile sperm count (β: −18.00 mil/ejaculate and standard error: 8.44, p = 0.033) in the setting of decreased semen volume (β: −0.35 ml, and standard error: 0.16, p = 0.035), but not sperm concentration, motility and morphology. These findings suggest a role for reproductive physicians and mental health providers to consider counselling men on the potential negative impact of stimulants prescribed for attention deficit hyperactivity disorder on semen volume during fertility planning.